La seule patrie est exil dans la langue - Serge Lesourd (EJP import test, 2016)
Summary: Man, this being of language, can never be fully and his desire originates from the original loss of a part of himself in the disappearance of his first lalangue. Thus, if the dream of man has in any time been to speak the same language to make himself understood, every attempt to talk the same language can only lead the terror. Making a detour via the theory of discourses of Lacan, the author demonstrates that the homeland remains the trace of this dream of a common language in which the loss would be abolished.
Keywords: Désir; Discours; Lalangue; Manque; Patrie